High Frequency Plant Regeneration, In Vitro Flowering of Solanum nigrum (L.)– An Important Antiulcer Medicinal Plant - C.V. Naidu2*, T.M. Sridhar1 and (Journal of Phytology, 2011)
An efficient protocol for direct shoot regeneration from axillary bud and shoot tip explants of Solanum nigrum is described. Healthy axillary bud, shoot tip explants were cultured on MS medium supplemented with different concentrations of BAP (0.5-3.0 mg/l) or Kn (0.5-3.0 mg/l) alone or in combination with IAA or NAA (0.5-1.0 mg/l). All the explants were responded effectively for regeneration.Ã‚Â Good regeneration frequencies were observed in all the combinations tested. High frequency and maximum number of multiple shoots was obtained in shoot tip culture, cultured on MS medium supplemented with 2.0 mg/l BAP+0.5mg/l IAA.The present investigation also describes role of auxins on successful induction of in vitro flowering from axillary bud, shoot tip and young leaf explants of Solanum nigrum. Maximum number of in vitro flowers (8) were obtained in shoot tip culture induced on MS medium supplemented with 3.0 mg/l Kn+0.5 mg/l IAA, followedÃ‚Â by 2.0 mg/l Kn+1.0 mg/l IAA, where maximum ofÃ‚Â six (6) flowersÃ‚Â per culture was obtained fromÃ‚Â axillary bud explant. All the in vitro raised shoots were transferred to MS rooting medium supplemented with 0.25-1.0 mg/l IBA. The best rooting response was observed in 0.5 mg/l IBA. The well rooted plantlets were transferred to polybags containing soil+vermiculite in 1:1 ratio for hardening. Finally the hardened plantlets were transferred to field conditions for maximum survivability.